Utilizing Digital Marketing As A Business Strategy: Utilizing Digital Marketing As A Business Strategy - Bintaro, B.P. Kusumo; Sokibi, Petrus; Amsyar, Izwan; Ayu Sanjaya, Yulia Putri (Pandawan Sejahtera Indonesia, 2022)
With the advancement of information technology has grown so rapidly. One form of development that can be seen in the existence of a platform that connects one another or what can be said is social media. Instagram, Facebook, Twitter and Tiktok are examples of social media that are the most popular platforms. Starting from children to adults all use social media[1]. With this, social media has become a concern for business people. Now, almost all business people do not hesitate to market their products or services through social media. On that basis, this article was written. The goal is to see how digital marketing is useful in today's business strategy.